Prevalence of the Peroneus Quartus Muscle and Its Association with Peroneal Tendon Pathologies: An MRI Study of 1160 Ankles - Yavuz Yuksel; Tarkan Ergun; Ozkan Kose (Diagnostics, 2025)
Background/Objectives: The peroneus quartus (PQ) muscle is a supernumerary muscle in the lateral compartment of the leg. Although frequently asymptomatic, it may contribute to peroneal tendon (PT) disorders due to mechanical crowding in the retromalleolar groove. This study aimed to determine the prevalence of the PQ muscle on MRI and assess its association with PT pathologies. Materials and Methods: This retrospective study evaluated 1160 ankle MRI scans from 1073 patients (mean age, 42.7 ± 14.5 years; 643 females, 430 males). The presence of the PQ muscle and associated PT pathologies, including tenosynovitis, tendinitis, and tendon tears of the peroneus brevis tendon (PBT) and peroneus longus tendon (PLT), was recorded. Statistical analyses were performed using chi-square tests, and associations were expressed as odds ratios (OR) with 95% confidence intervals (CI). Results: The PQ muscle was identified in 123 of 1160 ankles, corresponding to a prevalence of 10.6%. Its incidence was significantly higher in males (12.7%) than in females (9.2%) (p = 0.018), while the side distribution showed no statistically significant difference. PQ presence was associated with PBT pathology, particularly tendinitis and longitudinal tears, and with PLT tendinitis, whereas no clear association was observed with tenosynovitis or PLT tears. Conclusions: The PQ muscle is a relatively common anatomical variant, present in 10.6% of ankles on MRI scans. Its presence is significantly associated with PT abnormalities, especially PBT tendinitis and tears. Awareness of PQ may aid clinicians and radiologists in assessing lateral ankle pain and peroneal tendon disorders.